2005
DOI: 10.1063/1.2169444
|View full text |Cite
|
Sign up to set email alerts
|

Why Is Ice Slippery?

Abstract: In 1859 Michael Faraday postulated that a thin film of liquid covers the surface of ice—even at temperatures well below freezing. Neglected for nearly a century, the dynamics of ice surfaces has now grown into an active research topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
182
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(195 citation statements)
references
References 31 publications
3
182
0
5
Order By: Relevance
“…We account for this small decrease by calculating our liquid 1 (6) Unless otherwise noted, uncertainties listed for all values, and error bars on all figures, are the calculated standard errors (±1 SE) propagated from the measured relative standard error of each component.…”
Section: Calculationmentioning
confidence: 99%
“…We account for this small decrease by calculating our liquid 1 (6) Unless otherwise noted, uncertainties listed for all values, and error bars on all figures, are the calculated standard errors (±1 SE) propagated from the measured relative standard error of each component.…”
Section: Calculationmentioning
confidence: 99%
“…At the beginning (first 1-2ns), there is an increase of the energy but after that the energy remains approximately constant, apart from the thermal fluctuations. The analysis of the configurations of the TIP4P/2005 at T = 245 K, shows that the increase of energy during the first 1ns is due to the formation of a thin liquid layer at the surface of ice, which may indicate the onset of surface melting, mentioned already in the Introduction, and first proposed by Faraday [257]. The formation of a quasi liquid layer on the surface of ice below T m has been found both in experiment (see [258,259,260,261,262] and references therein) and in computer computer simulation for several potential models of water [263,264,265,266,92] and it has been explained by several theoretical treatments [258,260].…”
Section: Melting Point As Estimated From Simulations Of the Free Surfacementioning
confidence: 99%
“…The idea of pressure melting explaining ice friction has remained as common wisdom; however, it was already disputed upon publication by Faraday and Gibbs [3,4]. Later studies have confirmed that the pressures required are much too high for standard slippery scenarios, and ice friction is dominated by the spontaneous formation of a liquidlike premelt layer on the ice surface even well below freezing temperature [1,2]. Nonetheless, pressure melting is real and does play a role when the temperature is close to 0 C or the pressures involved are high.…”
mentioning
confidence: 99%
“…Not only does the amount of ice on the planet regulate global sea levels, melting ice plays a part in phenomena as diverse as the electrification of thunderclouds, frost heave, and slippery ice surfaces [1,2]. Early studies concluded that ice melts under moderate pressures, forming a thin water layer that is the source of ice's slipperiness.…”
mentioning
confidence: 99%